2015
DOI: 10.1155/2015/259603
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Process Variables via CFD to Evaluate the Performance of a FCC Riser

Abstract: Feedstock conversion and yield products are studied through a 3D model simulating the main reactor of the fluid catalytic cracking (FCC) process. Computational fluid dynamic (CFD) is used with Eulerian-Eulerian approach to predict the fluid catalytic cracking behavior. The model considers 12 lumps with catalyst deactivation by coke and poisoning by alkaline nitrides and polycyclic aromatic adsorption to estimate the kinetic behavior which, starting from a given feedstock, produces several cracking products. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…It can be seen in Cases 1, 2 and 4 that the catalyst is shifted toward the riser center in the injection zone due to the injected gas oil, which is in agreement with previous work reported by Li et al (2013) and Alvarez-Castro et al (2015). In Case 3 a better homogeneous catalyst distribution is observed, without catalyst accumulation in the riser center as compared to other cases, resulting in better flow distribution shown in Figure 2C.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It can be seen in Cases 1, 2 and 4 that the catalyst is shifted toward the riser center in the injection zone due to the injected gas oil, which is in agreement with previous work reported by Li et al (2013) and Alvarez-Castro et al (2015). In Case 3 a better homogeneous catalyst distribution is observed, without catalyst accumulation in the riser center as compared to other cases, resulting in better flow distribution shown in Figure 2C.…”
Section: Resultssupporting
confidence: 89%
“…The mesh is in agreement with previous Alvarez-Castro et al (2012) mesh tests shown in Table 3. The operating conditions used were taken from Chang et al (2012), shown in Table 4 and the component properties are the same used by Alvarez-Castro et al (2015), which were taken from Lopes et al (2011). The no slip condition on the wall was assumed for the gas phase and the free slip condition for the solid phase.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very important study, Alvarez-Castro et al 5 also reported a comparison of commercial data with model predictions. The predictions were based on a rigorous set of equations describing the hydrodynamics of the riser with CFD tools, used in tandem with a 12-lump kinetic model developed by Wu et al 6 These new methods permit the examination of the effect of unit operating conditions on the hydrodynamic features of the riser, feed conversion and product selectivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The latter was used by Lopes et al [22] to find out numerically that small changes in the riser outlet configuration impose a significant effect on the flow patterns and cracking product yields. Using CFD, Alvarez-Castro et al [23] evaluated the performance of a FCC riser based on product yield distribution and explored optimal conditions favoring a better flow homogeneity and attenuating unwanted core-annulus flow structure that often hinders gasoil conversion. Li et al [24] utilized the CFD methodology to show that the electrostatics had a weak influence upon the particle concentration, gas-phase temperature and product yield distribution in a reactive FCC riser.…”
Section: Introductionmentioning
confidence: 99%